VD_FINDINFO Décision / 2018 / 657 vom 13. August 2018 - VD Tribunal cantonal (2018)
PROCÈS ÉQUITABLE, PRINCIPE DE LA CÉLÉRITÉ | 6 CEDH, 6 par. 1 CEDH, 29 al. 1 Cst., 382 al. 1 CPP (CH), 393 al. 1 let. a CPP (CH)